Tracking control and identification of interaction forces for a rehabilitative training walker whose centre of gravity randomly shifts - Sun, Ping; Wang, Shuoyu; Chang, Hongbin (International journal of control, 2021)
This study investigates tracking control and the identification of interaction forces for a rehabilitative training walker whose centre of gravity randomly shifts. A stochastic model is structured to describe the motion of the walker subject to random parametric uncertainty. An observer is designed to identify the interaction forces, motion position, and motion velocity of the walker. The novelty of this approach is that the interaction forces are estimated from the reduced tracking performance rather than a conventional nonlinear function. Meanwhile, the position and velocity states are estimated based on the walker's position output. A nonlinear tracking controller is constructed to give the tracking and the estimation error systems mean-square stability both exponentially and practically. Furthermore, the mean-square errors of the interaction forces identification and the tracking motion converge to a sufficiently small neighbourhood upon tuning appropriate parameters. The results of a simulated application confirm the effectiveness of the proposed interaction forces identification and controller design method.